Pharmacological Activity, Pharmacokinetics, and Toxicity of Timosaponin AIII, a Natural Product Isolated From Anemarrhena asphodeloides Bunge: A Review - Lin, Yan; Zhao, Wai-Rong; Shi, Wen-Ting; Zhang, Jing; Zhang, Kai-Yu; Ding, Qian; Chen, Xin-Lin; Tang, Jing-Yi; Zhou, Zhong-Yan (Frontiers in Pharmacology, 2020)
Anemarrhena asphodeloides is a famous Chinese Materia Medica and has been used in traditional Chinese medicine for more than two thousand years. Steroidal saponins are important active components isolated from Anemarrhena asphodeloides. Among which, the accumulation of numerous experimental studies involved in Timosaponin AIII (Timo AIII) draws our attention in the recent decades. In this systematic review, we comprehensively summarized the pharmacological activity, pharmacokinetics and toxicity of Timo AIII. We found that Timo AIII presents multiple-pharmacological activities, such as anti-cancer, anti-neuronal disorders, anti-inflammation and anti-coagulant, etc. And the anti-cancer effect of Timo AIII in various cancers, especially hepatocellular cancer and breast cancer, is supposed as its most potential activity. The anti-inflammatory activity of Timo AIII is also beneficial to many diseases. Moreover, VEGFR, X-linked inhibitor of apoptosis protein (XIAP), B-cell-specific Moloney murine leukemia virus integration site 1 (BMI1), thromboxane (Tx) A2 receptor, mTOR, NF-κB, COX-2, MMPs and acetylcholinesterase (AChE), etc are identified as the crucial pharmacological targets of Timo AIII. Furthermore, the hepatotoxicity of Timo AIII was most concerned, and the pharmacokinetics and toxicity of Timo AIII need further studies in diverse animal models. In conclusion, Timo AIII is potent as a compound or leading compound for further drug development while still needs in-depth studies.